Learning Motivation Profile of Grade XI Science Students - Rahmaniah Aulia Disyaputri Siregar; Rahmi Nazliah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Learning motivation is an important factor in improving the quality of student learning. Therefore, this study aims to identify the learning motivation profile of grade XI science students in MA Alliful Ikhwan SAA. By knowing the learning motivation profile of biology students, efforts can be made to improve student learning motivation and the quality of biology learning at school. This research used a descriptive method with a quantitative approach. The research sample consisted of 72 students and 1 teacher in grade XI IPA 1, XI IPA 2, and XI IPA 3 at MA Alliful Ikhwan SAA. The instrument used was a learning motivation questionnaire that had been adapted from existing instruments. The data obtained were analyzed using descriptive statistical techniques. The results showed that the learning motivation of grade XI IPA 1 students reached 75.44%, with a strong motivation category. Meanwhile, grade XI IPA 2 and IPA 3 students had learning motivation results of 65.36% and 54.21%, respectively, with a high criteria. The overall average learning motivation results of grade XI IPA students reached 65.00% with a moderate category. In addition, the comparison of questionnaires submitted by the teacher showed that 72% of students had a high criteria in learning motivation. The implications of this research can provide benefits for biology teachers at MA Alliful Ikhwan SAA in improving student learning motivation and the quality of biology learning at school. Furthermore, this research can also be used as a reference for further research on student learning motivation in the field of biology.